Revisiting the foundations of fare evasion research. (July 2020) - Boyd, Colin
Highlights: The author's 1986 paper on tax compliance predicted that evasion shaped inspection output. That paper was never cited in the later literature on the effect of inspection on fare evasion. The theory in the 1986 paper is reintroduced so as to question modern models of fare evasion. Tipping points between multiple evasion levels may allow concentrated inspection. Manipulation of the perceived threat of inspection may reduce inspection costs. Abstract: In 1986 the author wrote a paper about tax compliance that theorized that the output of tax inspectors would be constrained by the rate of evasion of tax payments. That paper was never subsequently cited in the literature on transit fare evasion, which presumed that ticket inspection had a simple unidirectional effect on evasion. This current paper argues that all subsequent models of the economic link between fare evasion and ticket inspection overlook the possibility of a bidirectional relationship between the two. The 1986 paper further argued that multiple equilibrium levels of evasion versus inspection might be found to exist, and that evasion could therefore possibly theoretically be tipped from one level to another. This current paper suggests that the periodic concentrated deployment of inspectors might be a novel enforcement strategy that takes advantage of this phenomenon. The paper concludes with suggestions for the deceptive manipulation of passengers' perceptions of the probability of being detected as a fare evader.